Meridional variations in N* and Si* along 57°30′E and 47°E transects in the indian sector of the Southern Ocean during austral summer 2011. (August 2020) - Parli, Bhaskar V.; Dessai, Deepti R.G.; Anilkumar, N.; Chacko, Racheal; Pavithran, Sini
Abstract: The variations in nutrient utilization in the euphotic layer was studied using geochemical tracers N* (NO3 - −16PO4 3− ) and Si* (Si(OH)4 – NO3 - ) along two transect 57°30′E (T1) and 47°E (T2) during austral summer 2011 in the Indian Ocean sector of the Southern Ocean. Seawater samples collected from 8 depths within the euphotic zone (upper 200 m) along two meridional transects were analysed for nitrate, nitrite, silicate, phosphate and chlorophyll a (chl a ). Clear meridional differences in nutrient limitation were observed along the two transects. Depletion of silicate at Antarctic Zone (AZ) stations was 1.6 times higher in T1 than in T2. Significant inverse correlations were observed for N* ( p < 0.0001 ) and Si* ( p < 0.001 ) values with temperature and salinity implying that redistribution of preformed nutrients was influenced by hydrography. However, significant variances in Si* ( p < 0.001  at SSTF and p < 0.01  at PF-2) along the two transects could be attributed to differential uptake of silica by phytoplankton. Low Si* values were obtained at Polar Front 1 (PF1) and South Subtropical Front (SSTF) along T1 and from Sub Antarctic Front (SAF) to Polar Frontal Zone (PFZ) along T2. Although hydrography did have inverse correlation with tracers, the observed values indicate high consumption of silicate. Relatively higher Si* values in the north of SSTF coincided with lower abundance of diatoms in these waters. Conversely, high Si* values and abundance of diatoms at Antarctic Zone (AZ) indicate less consumption of Si. The biological consumption of nitrate was more clearly discerned in the northern region where nitrogen strongly limits the productivity both along T1 (39°S and the Agulhas Retroflection Front (ARF)) and T2 (40°S). Our observations suggest that much of the tracer distribution in these waters can be explained by the dominant phytoplankton groups, but influence of other biotic components on nutrient tracer distribution cannot be ruled out.